Regular sound change; The evidence of a single example - Adelaar, Alexander (Wacana, Journal of the Humanities of Indonesia, 2018)
The Neogrammarians of the Leipzig School introduced the principle that sound changes are regular and that this regularity is without exceptions. At least as a working hypothesis, this principle has remained the basis of the comparative method up to this day. In the first part of this paper, I give a short account of how historical linguists have defended this principle and have dealt with apparent counter evidence. In the second part, I explore if a sound change can be regular if it is attested in one instance only. I conclude that it is, provided that the concomitant phonetic (and phonotactic) evidence supporting it is also based on regularity. If the single instance of a sound change is the result of developments which are all regular in themselves, it is still in line with the regularity principle.